Reformulasi Pengaturan Debat Publik Pada Calon Tunggal Dalam Pilkada Berdasarkan Prinsip Efektivitas Pemilu - Kurnia, Evi; Virdaus, Saivol; Arifin, Zainal (Tolis Ilmiah : Jurnal Penelitian, 2025)
This study aims to determine the essence of the purpose of public debates in Regional Head Elections, as well as to reformulate the regulation of public debates for single candidates based on the principle of effectiveness. Public debates are an important tool in political campaigns that convey the vision, mission, and programs of candidates, as well as an instrument of political education for the community. However, the existence of a single candidate in the Pilkada poses a challenge to the effectiveness of the debate, due to the lack of substantive competition between candidates. This research uses normative legal research methods with statutory and conceptual approaches and is analyzed using primary and secondary legal materials. The results show that the provisions in Article 68 paragraph (1) and paragraph (3) PKPU Number 13 of 2024 still focus on procedural aspects and are not optimal in building public dialectical space. The proposed reformulation includes the addition of interactive question-and-answer sessions between candidates and the public and the involvement of independent panelists to increase the depth of the debate, as well as collaboration with the media to ensure live broadcasting of debates. This reformulation aims to maintain the substance of democracy, increase voter participation, and optimize the role of public debates as a medium for political education in Pilkada with a single candidate.